Conversion of a double-tetranuclear cluster silver helicate into a dihelicate via a rare desulfurization process. Issue 3 (22nd December 2021) - Fernández-Fariña, Sandra; González-Barcia, Luis M.; Romero, María J.; García-Tojal, Javier; Maneiro, Marcelino; Seco, José M.; Zaragoza, Guillermo; Martínez-Calvo, Miguel; González-Noya, Ana M.; Pedrido, Rosa
Abstract : We show the first example of a bisthiosemicarbazone silver double-tetranuclear cluster helicate [Ag4 L2 ]2 obtained by electrochemical synthesis which undergoes a rare desulfurization process giving rise to a cationic silver dihelicate [Ag2 (H2 L)2 ]SO4 . Abstract : We present the first example of a silver double-tetranuclear cluster helicate [Ag4 L2 ]2 obtained from a bisthiosemicarbazone ligand using electrochemical synthesis. This cluster helicate undergoes a rare desulfurization process in chloroform giving rise to a cationic silver dihelicate [Ag2 (H2 L)2 ]SO4 . This is the first silver mediated desulfurization reaction.